Penurunan Fatigue pada Pasien Kanker Paru dengan Progresive Muscle Relaxation - Anggraini, Desy; Rayasari, Fitrian; Fauziah, Munaya; Jumaiyah, Wati; Komalawati, Dedeh; Desy anggraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of progressive muscle relaxation on fatigue scores in lung cancer undergoing chemotherapy. This research method is quasi-experimental in the form of a Pre-Test and Post-Test with Control Group Design. The research showed an effect of progressive muscle relaxation on the fatigue score, p-value 0.000 < α 0.005. The dominant factor in fatigue is the frequency of chemotherapy. In conclusion, there is an influence of progressive muscle relaxation on fatigue scores. Keywords: Fatigue, Lung Cancer, Progressive Muscle Relaxation